Interactions between unfolding/disassembling behaviors, proteolytic subfragments and reversible aggregation of oxidized skeletal myosin isoforms at different salt contents. (July 2022) - Zhang, Min; Li, Chengliang; Zhang, Yuemei; He, Lichao; Li, Wei; Zhang, Mengling; Pan, Jiajing; Huang, Shuangjia; Liu, Yuanyi; Zhang, Yan; Jin, Yongguo; Cao, Jinxuan; et al.
Graphical abstract: Highlights: Salting is the key driving force toward swelling/rehydration of oxidized myosin. Myosin S1 and HMM subunits undergo both peptide oxidative scission and reversible assembling at 1–2% salt content. Up to 5% salt brining greatly induced solubilization and stabilization with cross-linkages at myosin rod portion. >3% salt improved elasticity and macroscopic viscosity of oxidized myosin during thermal gelation. Abstract: Myosin filament plays a critical role in water-trapping and thermodynamic regulation during processing of brined muscle foods. The redox state and availability of proteolytic/antioxidant enzymes affected by salt may change the ion-binding capacity of myosin consequently contributing to swelling and rehydration. Thus, this study investigated the impact of different salt content (0%, 1%, 2%, 3%, 4%, 5% NaCl) and oxidation in vitro (10 mM H2 O2 /ascorbate-based hydroxyl radical ( OH)-generating system) on the oxidative stability, solubility/dispersion capacity, chymotrypsin digestibility, aggregation site and the microrheological properties of isolated porcine myosin. The result showed that, brining at 2% salt exposed more sulfhydryl groups and inhibited the formation of disulfide bond, whereby smaller dispersed structure (diameter within 10–50 nm) and higher Ca 2+ -ATPase activity of the denatured myosin were observed. Accordingly, gel electrophoresis showed that myosin S1 and HMM subunits were highly oxidized and susceptible to reversible assembles. Despite enhanced hydrophobic interactions between swelled myosin at 3% salt content, ≥4% salt greatly promoted the exposure/polarization of tryptophan and cross-linking structures, mainly occurring at myosin S2 portion. The results of micro-rheology proved that oxidized myosin formed a tighter heat-set network following rehydration at high ion strength (≥4% salt), suggesting an increased inter-droplet resistance and macroscopic viscosity. This work is expected to give some useful insights into improved texture and functionality of engineered muscle foods.